Association between the dietary index for gut microbiota and metabolic syndrome in adults: the mediating role of body mass index - Hui Liu; Xin Xu; Zhicui Yao; Jialu Kang; Yongqing Shen; Wei Liu (Frontiers in Nutrition, 2025)
BackgroundDietary patterns influence the onset of metabolic syndrome (MetS) through the modulation of intestinal microbiota. Nevertheless, the relationship between the dietary index for gut microbiota (DI-GM), a novel metric for evaluating the link between diet and microbiota well-being, and its correlation with MetS, as well as the potential mediating role of body mass index (BMI), remains unclear.MethodsThis study examined information from 21,100 individuals participating in the National Health and Nutrition Examination Survey (NHANES) conducted between 2007 and 2020. The association of DI-GM with MetS was assessed using a weighted multivariate logistic regression model, and restricted cubic spline curves (RCS), subgroup analyses, and mediation analyses were performed.ResultsA significant inverse correlation was observed between DI-GM score and the prevalence of MetS. The prevalence of MetS decreased by 8% (OR = 0.92, 95% CI: 0.89–0.95) for each unit of DI-GM. The prevalence of MetS was reduced by 26% in Q4 compared with Q1 (OR = 0.74, 95% CI: 0.63–0.87). RCS analysis further revealed a linear relationship between DI-GM and MetS prevalence. Subgroup analysis showed that the negative association between DI-GM and MetS was more significant in the exercise, non-smoking, and non-drinking population. Furthermore, BMI played a significant mediating role in the association, accounting for 52.71%.ConclusionA notable negative correlation exists between DI-GM score and the prevalence of MetS. The promotion of a healthy lifestyle can strengthen this correlation, with BMI serving as a crucial mediating factor. This underscores the potential of dietary interventions that focus on gut microbiota in conjunction with weight management as targeted strategies for the prevention and management of MetS.